Simultaneous removal of arsenic and lead by iron phosphate and its potential for immobilization in mixed-contaminated soil - Kim, Han Na; Park, Jin Hee (Frontiers in Environmental Science, 2024)
Cationic metals such as lead (Pb) and metalloids such as arsenic (As) in contaminated soil can be simultaneously immobilized by iron phosphate because As(V) is stabilized by binding to iron(hydr)oxides and metals precipitate with phosphate. However, phosphate competes with As for sorption sites, which may affect simultaneous stabilization of Pb and As. Therefore, the purpose of this study was to evaluate simultaneous stabilization of As and Pb using iron phosphate both in single and multi-metal solution and soil. In both single and multiple element solutions, Pb was completely removed by the iron phosphate. Arsenic immobilization was explained by the Freundlich isotherm. Arsenate [As(V)] removal by iron phosphate decreased with increasing pH, while arsenite [As(III)] removal increased with increasing pH. The extraction of bioavailable As from the contaminated soil increased after incubation with iron phosphate, while the concentration of bioavailable Pb decreased. Increase of the bioavailable As can be attributed to As substitution by phosphate, which was not immobilized by iron. Although both As and Pb can be removed by iron phosphate in aqueous solution, a iron phosphate mineral with relatively low Ksp should be used to simultaneously immobilize As and Pb.